Ensaio clínico randomizado, controlado, comparando os resultados da bromoprida, metoclopramida e ondansetron aplicados intramuscular em dose única para o tratamento de vômitos em um pronto socorro pediátrico - Portela, Janete de Lourdes (2015)
Objective: To compare the effectiveness of single-dose intramuscular bromopride, metoclopramide, and ondansetron for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency for the treatment of vomiting in a pediatric emergency department setting. department setting. department setting. department setting. department setting. department setting.department setting. Methods: Randomized controlled trial of children who presented with vomiting due to gastroenteritis at the pediatric emergency department of Hospital Universitário de Santa Maria from August 2013 to June 2014. Children aged 1 to 12 years were randomized to receive a single intramuscular dose of bromopride or metoclopramide (up to 10 mg) or ondansetron (up to 8 mg) 0.15 mg/kg. After administration of the antiemetic drug, children remained under observation for at least 1 hour. Children who were discharged after the observation period were subsequently monitored by their parents or caregivers at home for 24 hours and contacted via telephone for assessment of the results of antiemetic therapy. The following parameters were compared across treatment groups: time to cessation of vomiting within 1, 6, and 24 hours; acceptance of oral rehydration therapy; intravenous fluid replacement; return to hospital; and adverse effects attributable to the antiemetic. All parents or caregivers were given information on the antiemetic treatment that would be provided and signed an informed consent form authorizing the child's participation in the study. Results: Of 180 children randomized, 175 completed the trial. Within 1 hour of antiemetic administration, cessation of vomiting had been achieved in 96.6% of children given bromopride, 94.8% of those given metoclopramide, and 100% of those given ondansetron (p=0.312). Six hours after administration, bromopride was found to cease vomiting in 216±114 minutes, metoclopramide in 150±168 minutes, and ondansetron in 72±54 minutes (p=0.011). Cessation of vomiting at 24 hours was achieved in 67.8% of children given bromopride, 67.2% of those given metoclopramide, and 96.6% of those given ondansetron (p=0.002). Children in the ondansetron group accepted more fluid replenishment orally (200 ml) than those given bromopride or metoclopramide (150 ml and 100 ml respectively) (p=0.034). Eleven children ultimately required intravenous fluids: five in the bromopride group and six in the metoclopramide group. Within 1 hour of antiemetic administration, only 24.1% of children in the ondansetron group reported adverse effects (somnolence, diarrhea, fatigue, restlessness, feeling hot) fatigue, restlessness, feeling hot) fatigue, restlessness, feeling hot)fatigue, restlessness, feeling hot)fatigue, restlessness, feeling hot)fatigue, restlessness, feeling hot) fatigue, restlessness, feeling hot) fatigue, restlessness, feeling hot) fatigue, restlessness, feeling hot)fatigue, restlessness, feeling hot) fatigue, restlessness, feeling hot) fatigue, restlessness, feeling hot)fatigue, restlessness, feeling hot)fatigue, restlessness, feeling hot) fatigue, restlessness, feeling hot)fatigue, restlessness, feeling hot) , whereas 42.4% and 44.8% of children in the bromopride and metoclopramide groups respectively reported somnolence (p=0.034). At 24 hours, there were no significant differences in adverse effects across the three groups (p=0.357). Conclusion: In a pediatric emergency department setting, ondansetron is superior to bromopride and metoclopramide for treatment of vomiting. Ondansetron was associated with cessation or reduction of vomiting both within 1 hour of administration and at 6 and 24 hours. Bromopride and metoclopramide were both effective, but were associated with somnolence, an adverse effect that can prolong observation time in the emergency department and thus increase hospital costs.